Application of Data Mining in the Best Classification of Animal Feed Types - Purwa Hasan Putra (INFOKUM, 2022)
The company's goal is to produce high quality aquaculture products such as feed, seeds, pet feed, probiotics to shrimp products and processed food for the domestic and export markets. The company is still experiencing difficulties in determining the appropriate composition for the manufacture of animal feed. So that the animal feed produced has poor quality. Therefore, we need a decision support system that can assist in the process of determining the composition in the manufacture of animal feed. Because Data Mining is a computer-based system capable of solving unstructured problems. To be able to assist in the process of determining the composition of the company's animal feed, the author uses the Multi Factor Evaluation Process method. The Multi Factor Evaluation Process method is a method that breaks up a complex, unstructured situation into its component parts, the Multi Factor Evaluation Process method is a specification of the problem, in which decision makers must evaluate each alternative with multiple specific criteria. From the results of the study, it can be concluded, among others: The company must provide supporting equipment to run the application of the MFEP Method in Determining the Composition of this Feed so that it runs as desired. To achieve the purpose of the application of the MFEP Method Application in Determining the Composition of Animal Feed that is designed, it is hoped that this research can continue so that the system can be based on Client-Server and Online.